Pendampingan Digitalisasi UMKM “Warung Ana” Dalam Upaya Pengembangan Usaha Di Era Digital - Rosiana Agussetyaningsih; Aufa Izzudin Baihaqi (Politeknik Negeri Fakfak, 2024)
UMKM (Micro, Small and Medium Enterprises) in Indonesia are one of the sector factors that dominate business actors. However, currently UMKM are experiencing challenges in facing digitalization competition in the business sector, in order to survive and develop, business actors must be able to keep up with the times and be able to utilize and apply social media. UMKM Digitalization Assistance aims to help develop businesses that are unable to compete due to the lack of knowledge and experience possessed by business actors. From the assistance provided by the author, Warung Ana was able to develop and slowly expand the scope of its market share through the social media that the author produces.